(3GdEKHGJ aj Gdabg GdESdGej hGdCfXeI GdSYhOjI (B:s (3eGgjI GdEKHGJ hWHjYJg GdfXGejI hGdabgjI (B: (3hSGFd GdEKHGJ aj fXGe GdeQGaYGJ GdTQYjI GdSYhOj hCMcGe Gdabg GdESdGej (B/s - (3eUWai, MSGe GdOjf SdjeGf Jhajbs ((3GdQjGV ;s (3GdLjRI, eUQ (B:s (3OGQ GdcJGH GdLGeYj ddfTQ hGdJhRjY,s, 2018)
(3jJfGhd cJGH (B((3GdEKHGJ aj Gdabg GdESdGej hGdCfXeI GdSYhOjI(B) (3hGdPj bGe HJCdjag (B((3MSGe GdOjf SdjeGf Jhajb(B) (3aj MhGdj (B(291) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdEKHGJ Hjf Gdabg hGdbGfhf aj GdSYhOjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3ebOeI, GdHGH GdChd (B: (3GdeHGOF GdYGeI ddEKHGJ GdbVGFj, hjTed GdaUd GdChd (B: (3eGgjI GdEKHGJ hWHjYJg GdabgjI hGdfXGejI, GdaUd GdKGfj (B: (3COdI GdEKHGJ aj Gdabg GdESdGej hGdfXGe, GdaUd GdKGdK (B: (3TQhW GdhGbYI eMd GdEKHGJ aj Gdabg GdESdGej hGdfXGe(B... (3EdN(B.s
(3GdeMJhjGJ (B: (3GdHGH GdChd (B: (3GdeHGOF GdYGeI ddEKHGJ GdbVGFj, GdaUd GdChd eGgjI GdEKHGJ hWHjYJg GdabgjI hGdfXGejI (B...-(3GdHGH GdKGfj (B: (3WQb GdEKHGJ GdbVGFj aj Gdabg GdESdGej hfXGe GdeQGaYGJ, GdaUd GdChd GdEKHGJ HGdcJGHI aj Gdabg GdESdGej hGdfXGe, GdaUd GdKGfj GdEKHGJ HTgGOI GdTghO, GdaUd GdKGdK(B: (3GdEKHGJ HGdbQGFf hMLjI GdCeQ GdeLOj, GdaUd GdQGHY(B: (3GdEKHGJ HGdEbQGQ GdbVGFj aj Gdabg GdESdGej hGdfXGe, GdaUd GdNGeS GdEKHGJ HGdjejf aj Gdabg GdESdGej hGdfXGe (B... (3hehVhYGJ CNQi(B.s
(3HHdjhLQGajI (B: (3UaMI (B273-288.s
Keywords: (3GdEKHGJ (B((3abg ESdGej(B)s; (3GdEKHGJ (B((3bGfhf(B)s -- (3GdSYhOjIs; (3bGfhf GdeQGaYGJs -- (3GdSYhOjIs; (3GdOaGY Yf GdeJge (B((3ELQGAGJ eOfjI(B)s -- (3GdSYhOjIs; (3GdeQGaYGJs; (3GdEKHGJ GdbVGFjs; (3TgGOI GdTghOs; (3GdEKHGJ GdEdcJQhfjs